ANTITUMOR DRUG ELLIPTICINE INHIBITS THE ACTIVITIES OF RAT HEPATIC CYTOCHROMES P450 - Aimova, Dagmar; Stiborova, Marie (Biomedical papers, 2005)
Ellipticine is a potent antineoplastic agent, whose mode of action is considered to be based mainly on DNA intercalation and/or inhibition of topoisomerase II. Recently, we found that ellipticine also forms the cytochrome P450 (CYP)-mediated covalent DNA adducts. Here, we study the effect of ellipticine on CYP enzymes in rat hepatic microsomes, studying its binding to the enzymes and its potential to inhibit the CYP activities measured with their selective substrates. Although ellipticine was reported to be a selective and strong inhibitor of CYP1A1/2, we found that its inhibitory potential is non-specific. Ellipticine is the most potent inhibitor for CYP3A-dependent 6β-hydroxylation of progesterone, followed by CYP1A1/2-dependent ethoxyresorufin O-deethylation and CYP2B-mediated pentoxyresorufin O-depentylation. Lower inhibition was detected for 1'-hydroxylation of bufurarol, 21-hydroxylation of progesterone and 6-hydroxylation of chlorzoxazone catalyzed by CYP2D, CYP2C and CYP2E1, respectively. Ellipticine binds to several CYPs of rat hepatic microsomes. The binding titration of ellipticine typically give reverse type I spectrum with CYPs in rat hepatic microsomes. The results indicate that inhibition of CYPs by ellipticine cannot be explained only by its differential potency to bind to individual CYPs.
Keywords: Ellipticine/Anticancer drug/Cytochrome P450/Inhibition/Binding